Zawód sędziego w Polsce w latach 1918-1939 - Małgorzata Materniak-Pawłowska (Czasopismo Prawno-Historyczne)
In the interwar period 1918-1939 the profession of a judge was subject to constant transformations being a result of numerous amendments to the legal regulations governing that profession. First, until 1928, the foreign laws that earlier governed in the partitioned territories of Poland had continued to apply, with only some minor modifications implemented by the Polish legislature. Later on, from 1 January 1929 and until the outbreak of the Second World War in 1939 all issues pertaining to the judicial profession were subject to common judicature uniformly applied throughout the whole country.